RESEARCH ON MONITORING METHOD AND APPLICATION OF THE DYNAMIC CONTACT FORCE BETWEEN CATENARY AND PANTOGRAPH BASED ON STRAIN RESPONSE INVERSION TECHNOLOGY (MT) - LEI YuHeng; REN Liang; LIU QiangPing; YOU RunZhou; XIA MengYing; LI HongNan (Jixie qiangdu)
In-situ monitoring of the dynamic contact force between catenary and pantograph is very important for the quality evaluation of pantograph catenary current collection. A monitoring method based on strain response was proposed to invert the value and position of the dynamic contact force between catenary and pantograph. The measurement principle, sensor installation method and calibration experiment of key parameters were described in detail. The monitoring system has been successfully applied to a metro test project with rigid overhead catenary. And the dynamic contact force between pantograph and catenary was monitored and analyzed when the subway was running at the speed of 60 km/h and 80 km/h, respectively. The results indicated that the dynamic contact force measurement method based on strain response has the advantages of high measurement accuracy, good data consistency and flexible sensor installation. It can not only accurately restore the value of dynamic contact force between catenary and pantograph, but also locate the position of the dynamic contact force on the carbon slide of pantograph. This work can effectively evaluate the performance quality of the coupling system of pantograph and catenary.